A comparative study of 0.4% ripasudil, 0.02% netarsudil, and 0.5% timolol in combination with 0.005% latanoprost in the medical management of primary open-angle glaucoma or ocular hypertension - Tirupati Nath,; Snigdha Sen,; Himanshu Kumar Yadav,; Dinesh Kumar Yadav, (Asian Journal of Medical Sciences, 2024)
Background: Globally, it is expected that 111 million people will have glaucoma by 2040. Intraocular pressure (IOP) is the most crucial clinical risk factor for glaucoma onset and/or progression. Aims and Objectives: The aim of the study is to compare 0.4% ripasudil, 0.02% netarsudil, and 0.5% timolol in combination with 0.005% latanoprost in the medical management of primary open-angle glaucoma (POAG) or ocular hypertension (OHT). Materials and Methods: The prospective randomized clinical study was conducted on patients with mild-to-moderate POAG or OHT on a single prostaglandin analog (e.g., latanoprost) not achieving target IOP. Patients with narrow-angle glaucoma, any ocular surgery, and advanced glaucoma were excluded from the study. Patients were followed up at 15 days, 1 month, 2 months, and 3 months for a complete ophthalmic examination. Results: The maximum number of patients showed 41–60 years of age group. The male–female ratio was 1.8:1. A mild-to-moderate adverse event in the form of conjunctival hyperemia was seen in all groups. The mean reduction in IOP (mmHg) from baseline to 3 months in Groups A, B, and C is 5.7±0.923, 7.11±0.832, and 6.83±0.707 mmHg, respectively. Conclusion: When given in combination with 0.005% latanoprost and comparing IOP reduction in terms of efficacy, 0.4% ripasudil and 0.02% netarsudil are almost similar, but ripasudil was well tolerated and showed minimal ocular adverse effects; hence, ripasudil is better in comparison to netarsudil.